Inhibiting Ion Migration by Guanidinium Cation Doping for Efficient Perovskite Solar Cells with Enhanced Operational Stability. Issue 6 (24th February 2022) - Li, Zhipeng; Hao, Lianzheng; Liu, Dachang; Sun, Xiuhong; Zhao, Qiangqiang; Shao, Zhipeng; Chen, Chen; Wang, Xiao; Wang, Li; Cui, Guanglei; Pang, Shuping
Abstract : Perovskite solar cells (PSCs) develop great potential to make photovoltaic power generation systems more cost‐effective due to the high power conversion efficiency (PCE), low material cost, and easy fabrication. Alloyed A‐site cations surrounded by PbI6 octahedra play decisive roles in the crystal structure, bandgap, and phase stability, as well as ion migration. Herein, based on the temperature‐dependent ion conductivity measurement, the activation energy for iodide ion migration is systematically studied with different proportions of guanidinium cation (GA + ) substitution. It is found that partial GA + doping could effectively suppress iodide ion migration. The triple‐cation perovskite (MA0.8 FA0.1 GA0.1 PbI3 ) PSCs achieve a PCE of 22.17% with superior operational stability maintaining 90% of their initial efficiency after 1200 h under continuous light soaking. Furthermore, it is extended to mini perovskite solar modules, 14 cm 2 active area, and achieves a PCE of 19.18%. Abstract : The effect of A‐site doping with guanidinium cation (GA + ) on ion migration is explored based on the temperature‐dependent ion conductivity. The increase of activation energy proves the lift of ion migration barrier. It elaborates that doping of GA + can effectively suppress the ion migration and enhance the operational stability of the device.